Instrumentation of erosion function apparatus and evaluation of a new erosion characterization methodology - Tran, Tri Van (Kansas State University, 2018)
Surface soil erosion is a widespread problem that impacts the natural and built environment. Many disciplines, such as hydrology, soil science, agriculture, and geotechnical engineering, have investigated soil erosion. Although empirical equations to predict soil erosion exist, they are typically inaccurate, so several devices have been developed to quantify the erodibility of soil. The erosion function apparatus (EFA) was developed to predict the erosion potential of soil for evaluating bridge scour; however, it has been used for several other geotechnical applications. The main disadvantages of the EFA are that it is unable to directly measure the shear stress, it remains operator dependent, and it is time consuming as a standard test requires at least eight hours. Moreover, as erosion occurs, it affects the water quality and makes it difficult to observe the soil sample surface during the test, affecting the operator judgement. The research objective of this project is to instrument the EFA to address the limitations of the device. A stereo-photogrammetry system was developed to measure the soil surface roughness following an EFA test and reduce operator dependency. Turbidity sensors were added to provide a secondary measurement of erosion. The newly instrumented EFA was used to develop a new methodology for interpreting erosion results. Lastly, the new methodology and instrumentation were used to explore the influence of natural and engineered soil properties on soil erosion.
Keywords: Erosion; Critical shear stress; Erosion function apparatus; Instrumentation; Hydraulic shear stress